Caregiver perspectives on the impact of uncertainty on the everyday lives of autistic children and their families. (May 2022) - Goodwin, Jane; Rob, Priyanka; Freeston, Mark; Garland, Deborah; Grahame, Victoria; Kernohan, Ashleigh; Labus, Marie; Osborne, Malcolm; Parr, Jeremy R; Wright, Catharine; Rodgers, Jacqui
Approximately 50% of autistic children experience high anxiety. Intolerance of uncertainty (tendency to react negatively to uncertain situations) is a key mechanism in the development and maintenance of anxiety. This study aimed to provide a descriptive, thematic analysis of the impact on uncertainty on the daily lives of autistic children and their families. Semi-structured interviews were conducted with parents and caregivers of 53 autistic children (including 3 dyads) aged 6–16 years to elicit examples of uncertain situations that the children found challenging and to explore the impact of these situations on family life. Thematic analysis revealed five overarching themes: child's reactions to uncertainty, trying to reduce uncertainty, the impact of difficulties with uncertainty, the impact of uncertainty on parenting and the impact on parents. These findings provide a crucial understanding into the range of uncertain situations autistic children with anxiety experience. Anxiety-reduction approaches based on increasing tolerance to everyday uncertain situations could help improve well-being, quality of life and participation for autistic children and their families. Lay abstract: Anxiety is common in autistic children. Research shows that this may be related to intolerance of uncertainty, which is a tendency to react negatively to uncertain situations. Understanding when, why and how autistic children respond to uncertainty is important in the development of anxiety programmes. We asked 53 (including 3 dyads) parents of autistic children about the types of uncertain situations that cause difficulties for their child and how uncertainty impacts on daily life for them and their families. We found that uncertain situations made autistic children and their families feel sad, worried, frustrated and angry through the themes: child's reactions to uncertainty, trying to reduce uncertainty, the impact of difficulties with uncertainty, the impact of uncertainty on parenting and the impact on parents. There are lots of situations that are anxiety provoking for autistic children because of uncertainty, such as school. Programmes to reduce anxiety and increase autistic children's ability to cope with everyday uncertain situations could improve quality of life for autistic children and their families.